2017
DOI: 10.1126/science.aam9321
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid detection with CRISPR-Cas13a/C2c2

Abstract: Rapid, inexpensive, and sensitive nucleic acid detection may aid point-of-care pathogen detection, genotyping, and disease monitoring. The RNA-guided, RNA-targeting CRISPR effector Cas13a (previously known as C2c2) exhibits a “collateral effect” of promiscuous RNAse activity upon target recognition. We combine the collateral effect of Cas13a with isothermal amplification to establish a CRISPR-based diagnostic (CRISPR-Dx), providing rapid DNA or RNA detection with attomolar sensitivity and single-base mismatch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
3,003
4
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 2,713 publications
(3,042 citation statements)
references
References 33 publications
25
3,003
4
10
Order By: Relevance
“…This HEPN-activated conformation of Cas13 is a general nuclease, which is capable of cleaving either the RNA molecule that it was activated by ( cis cleavage), or any other RNA molecule that it happens to encounter ( trans / collateral cleavage). All Cas13 proteins characterized to date exhibit these behaviors (Abudayyeh et al, 2016; East-Seletsky et al, 2016; East-Seletsky et al, 2017; Gootenberg et al, 2018; Gootenberg et al, 2017; Konermann et al, 2018; Smargon et al, 2017; Yan et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This HEPN-activated conformation of Cas13 is a general nuclease, which is capable of cleaving either the RNA molecule that it was activated by ( cis cleavage), or any other RNA molecule that it happens to encounter ( trans / collateral cleavage). All Cas13 proteins characterized to date exhibit these behaviors (Abudayyeh et al, 2016; East-Seletsky et al, 2016; East-Seletsky et al, 2017; Gootenberg et al, 2018; Gootenberg et al, 2017; Konermann et al, 2018; Smargon et al, 2017; Yan et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…The RNA-activated RNA cleavage behavior of Cas13 provides a mechanism for RNA detection and diagnostic applications (East-Seletsky et al, 2016; Gootenberg et al, 2018; Gootenberg et al, 2017), as well as RNA-targeting in heterologous systems (Abudayyeh et al, 2017; Aman et al, 2018; Cox et al, 2017; Konermann et al, 2018). Versions of Cas13 where the HEPN-domains have been catalytically inactivated (Abudayyeh et al, 2016; East-Seletsky et al, 2016; Konermann et al, 2018; Smargon et al, 2017; Yan et al, 2018) (deactivated Cas13; dCas13) have shown to be useful as programmable RNA binding proteins for RNA imaging (Abudayyeh et al, 2017), RNA editing (Cox et al, 2017) and regulating specific transcripts RNA in other ways (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA-targeting CRISPR-associated enzyme Cas13(1, 2) has recently been adapted for such purpose. This detection platform, termed SHERLOCK ( S pecific H igh Sensitivity E nzymatic R eporter Un LOCK ing) (3), can discriminate between inputs that differ by a single nucleotide at very low concentrations and can be lyophilized for portable deployment. However, this technology has several limitations, including the lack of quantitation and reliance on fluorescent detection equipment for readout.…”
mentioning
confidence: 99%
“…8 Because it is desirable to optimize detection speed, sensitivity, selectivity, and cost for bacterial diagnostics, research into bacterial detection continues to be of substantial interest. 5,911 …”
mentioning
confidence: 99%